P28. A set of HU for "Exact IGRT" couch in Eclipse TPS. (December 2016) - Mazoyer, F.; Gonod, M.; Petitfils, A.; Bidault, F.; Naudy, S.
Abstract : Introduction: The planning system Eclipse contains a couch model library. The objective of this study is to determine the HU parameters to apply for the Exact IGRT couch. The validity of these parameters was also examined with a comparison of the impact of the couch on the calculated and measured dose. Materials and methods: Couch modeling of the "Exact IGRT" is customizable with two adjustable parameters by user: the Hounsfield units of the internal structure and those of external structure. A CT scan image was acquired and HU of these structures was measured. The obtained set of HU was used for dose calculation with couch modeling. Impact of the presence of the dose of 6 MV and 18 MV direct beams was evaluated with a calculation performed with Acuros XB V11 (Varian) with and without the couch. Results are compared to the measure. The thin and thick models were considered. Results: Hounsfield units of the internal structure were measured at −945 ± 5. Those of the external structure were measured at −300 ± 20. Differences between the calculated dose with and without thin couch modeling were respectively 1.8% and 1.0% for the 6 MV and 18 MV beams. For the thick model, differences were 2.4% and 1.4%. During measurements, the difference was established at 1.8% and 1.1% for the thin part of couch (landmark H4) and 2.1% and 1.0% or the thick part of couch (landmark H0). Conclusions: The results show a good correlation between calculated and measured dose difference. Geometrical model build-in the planning system Eclipse associated with the determined HU enable a correct modeling of treatment couch.